Proceedings of the Conference on Fairness, Accountability, and Transparency 2019
DOI: 10.1145/3287560.3287575
|View full text |Cite
|
Sign up to set email alerts
|

Racial categories in machine learning

Abstract: Controversies around race and machine learning have sparked debate among computer scientists over how to design machine learning systems that guarantee fairness. These debates rarely engage with how racial identity is embedded in our social experience, making for sociological and psychological complexity. This complexity challenges the paradigm of considering fairness to be a formal property of supervised learning with respect to protected personal attributes. Racial identity is not simply a personal subjectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 40 publications
0
81
0
Order By: Relevance
“…Although such a design is derived from the naturally occurring labels of the crawled and referenced datasets, the selected groupings have inherent limitations. Unlike the Pilot Parliaments Benchmark from the Gender Shades study [6] where the intersectional groups are defined with respect to skin type, "ethnicity" is an attribute that is highly correlated but not deterministically linked to racial categories, which are themselves nebulous social constructs, encompassing individuals with a wide range of phenotypic features [3]. Similarly, binary gender labels are compatible with the format of commercial product outputs, but exclusionary of those not presenting in the stereotypical representations of each selected gender identity [29].…”
Section: Tensionmentioning
confidence: 99%
“…Although such a design is derived from the naturally occurring labels of the crawled and referenced datasets, the selected groupings have inherent limitations. Unlike the Pilot Parliaments Benchmark from the Gender Shades study [6] where the intersectional groups are defined with respect to skin type, "ethnicity" is an attribute that is highly correlated but not deterministically linked to racial categories, which are themselves nebulous social constructs, encompassing individuals with a wide range of phenotypic features [3]. Similarly, binary gender labels are compatible with the format of commercial product outputs, but exclusionary of those not presenting in the stereotypical representations of each selected gender identity [29].…”
Section: Tensionmentioning
confidence: 99%
“…40 In machine learning, fairness encompasses concerns about how data-driven approaches can reflect and perpetuate biases rooted in social inequality and discrimination. 41,42 A model's predictions can vary systematically across demographic groups if, for example, the data being sampled reflects societal inequalities (i.e. historical bias) or if the sampling methods result in the underrepresentation of certain groups (i.e.…”
Section: Machine Learning Models: Performance Versus Interpretabilitymentioning
confidence: 99%
“…Their study showed that there are gaps when using three different semantic representations such as bag-of-words, Deep Recurrent Neural Networks (DRNN), and word embedding [38]. Benthall and Haynes have investigated supervised learning algorithms and revealed that they are exposed to racial bias because of the differentiation that is embedded in systematic patterns [39].…”
Section: B Population Biasmentioning
confidence: 99%